EFFECT OF FINANCIAL STRESS & FINANCIAL BEHAVIOR ON AN INDIVIDUAL’S FINANCIAL WELL-BEING IN QUETTA: MEDIATING ROLE OF FINANCIAL ATTITUDE (Al-Aasar, 2026)
This study examines the relationship between financial stress, financial behavior, and financial well-being among individuals in Quetta, Pakistan, with financial attitude serving as a mediating variable. Using a quantitative research design, data were collected from 384 respondents through structured questionnaires administered across four major towns of Quetta. The study employs Structural Equation Modeling (SEM) through SmartPLS to test the hypothesized relationships. Findings reveal that financial stress negatively affects financial well-being, while positive financial behavior enhances it. Financial attitude partially mediates the relationship between financial stress and financial well-being and between financial behavior and financial well-being. The results underscore the importance of psychological factors in determining financial outcomes in a developing country context. This research contributes to the limited literature on financial well-being in Balochistan and offers practical implications for policymakers, financial institutions, and educators seeking to improve population-level financial wellness.